2022
DOI: 10.3389/fenvs.2022.918485
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Waste: The Meaning of Product’s Attributes and Food-Related Lifestyle

Abstract: The increasing volume and value of food waste is a huge threat to achieving sustainable development, food market stability, human population growth, and people’s well-being. Considering that consumers are responsible for a large degree of food waste, the current study looks at the problem of household food waste from the perspective of both food product attributes and consumers’ lifestyles. Specifically: How do people differ in their food disposal inclination based on their food-related lifestyle and products’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
0
6
0
3
Order By: Relevance
“…Consumer attitudes regarding food waste in Poland were studied by Bilska et al, (2020, Szymkowiak et al, (2022), Tarczyńska et al, (2023 and Tomaszewska et al, (2020).…”
Section: Resultsmentioning
confidence: 99%
“…Consumer attitudes regarding food waste in Poland were studied by Bilska et al, (2020, Szymkowiak et al, (2022), Tarczyńska et al, (2023 and Tomaszewska et al, (2020).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that household food waste behaviour is influenced by various factors and interdependencies (BCFN, 2012;Gustavsson et al, 2011;Szymkowiak et al, 2022). To analyse food waste in a more systematic way, a conceptual framework will be adopted.…”
Section: Reasons For Household Food Wastementioning
confidence: 99%
“…In addition, other motivations supporting policy makers to develop specific interventions could be detected. Among these, the most significant are: i) a good level of social capital of the territories allows FW to be reduced [58]; ii) good stock organization of the kitchen or fridge can help consumers to better manage their food stocks so avoiding wastes [74,77]; iii) packaging size can influence consumer purchasing behaviour and support efficient food use [78,79].…”
Section: Plos Onementioning
confidence: 99%